ANALISIS KESULITAN SOAL CERITA BERDASARKAN TEORI NEWMAN PADA MATERI BILANGAN CACAH KELAS V SD NEGERI BLEKATUK PURWOREJO - Muslih, Muhammad; Suyoto, Suyoto; Ratnaningsih, Arum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to 1) Describe the difficulty of story problems based on Newman's theory of whole number material for grade V of SDN Blekatuk, 2) Know the factors that influence students to solve story problems based on Newman's theory of whole number material for grade V of SDN Blekatuk. This study uses a descriptive qualitative research method. The subjects of this study were 23 fifth grade students of Blekatuk State Elementary School and 5 students were taken according to high, medium and low difficulty. Data collection techniques were observation, interviews, documentation, and data recording cards. The research instrument used data recording cards, observations and interviews. The results of the study showed that: 1) students with high difficulty, subject 1, had not been able to understand the problem, transformation, process skills and writing answers. While students with subject 2 had not met the indicators of understanding the problem, students had difficulty performing process skills and writing answers. Students with moderate difficulty were two students, subjects 3 & 4 had not met the indicators of understanding the problem, students had difficulty performing process skills and writing answers. One student with low difficulty had not met the indicators of understanding the problem. 2) Internal and external factors influencing students' difficulties in solving word problems on whole numbers: internal factors, interest in learning mathematics, attitudes toward learning mathematics, and motivation to learn mathematics. External factors, learning methods and media, classroom atmosphere, and family environment.